2012
DOI: 10.1002/cctc.201100473
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Coke Precursors in a Pd Lattice: A Carbon‐Supported Heteropoly Acid Catalyst for the Dehydration of Glycerol into Acrolein

Abstract: Supported heteropoly acid catalysts are frequently used in the dehydration of glycerol into acrolein because of their high activity. However, they are easily deactivated by coke that can become deposited on the catalyst surface. Herein, we report a technique that significantly decreases coke formation by capturing coke precursors in a Pd lattice. The Pd‐added H3PW12O40/C catalyst (Pd‐PWC) showed stable catalytic activity and the amount of deposited coke formed was decreased to about 40 % of that without Pd add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The catalyst deactivation is mainly due to extensive coke deposition on the active sites of the catalyst . Methods including adding O 2 to inhibit the rate of coking, modifying catalysts by adjusting acid strength and distribution, and amplifying catalyst pore size have slightly extended the catalyst life, but none has been convincingly successful .…”
Section: Results Of Glycerol Dehydration In Sc‐co2 and Gas‐phase Co2 mentioning
confidence: 99%
See 1 more Smart Citation
“…The catalyst deactivation is mainly due to extensive coke deposition on the active sites of the catalyst . Methods including adding O 2 to inhibit the rate of coking, modifying catalysts by adjusting acid strength and distribution, and amplifying catalyst pore size have slightly extended the catalyst life, but none has been convincingly successful .…”
Section: Results Of Glycerol Dehydration In Sc‐co2 and Gas‐phase Co2 mentioning
confidence: 99%
“…[1b, 2] The catalystd eactivation is mainly due to extensive coke deposition on the activesites of the catalyst. [5] Methods including adding O 2 to inhibit the rate of coking, [6] modifying catalysts by adjusting acids trength and distribution, [7] and amplifying catalyst pore size have slightly extended the catalyst life, but none has been convincingly successful. [8] Catalyst regeneration by coke combustion has also been attempted, but the catalystw as quickly deactivated again in at imeframe unsustainable for industriala pplications.…”
mentioning
confidence: 99%
“…Similar observations were detected by Yi's group who investigated the activity, selectivity and stability of Pd-added H 3 PW 12 O 40 /C catalyst in the dehydration of glycerol. [41] Nevertheless, the introduction of any additional gas into the reactor will increase the cost price of the resulting product and tighten the requirements for the reactor equipment. Our group demonstrated that commercial reforming catalysts Pt/γ-Al 2 O 3 exhibited an excellent selectivity to acrolein and stability to deactivation without introducing any carrier gas into the reactor.…”
Section: Doping With Noble Metalsmentioning
confidence: 99%
“…20 Hence, it is imperative to employ an appropriate support to distribute the heteropoly acid. [21][22][23][24][25] Kaolin, a clay mineral which is abundant on the earth, it is composed of abundantly 1 : 1 clay mineral Al 2 Si 2 O 5 (OH) 4 structure per alumina-silicate producing bulky congested particles of SiO 4 tetrahedral sheets and AlO 2 (OH) 4 octahedral sheets. 26,27 Kaolin clay are promising supports due to their common fascinating features, such as their inherent acidity, excellent thermal stability and easily controlled structural morphology.…”
Section: Introductionmentioning
confidence: 99%